The Effectiveness of the ITE Law in Protecting the Right to Privacy in the Digital Era - Dewi Tjandraningsih; Juhary Ali (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2025)
This study examines the effectiveness of Indonesia’s Electronic Information and Transactions Law (UU ITE) in protecting citizens’ right to privacy in the digital era. As digital platforms increasingly collect, store, and process personal data, concerns over privacy violations have become more complex. The research highlights several challenges, including limited legal definitions of personal data, inadequate enforcement mechanisms, and technological risks related to data breaches and cyber surveillance. Although UU ITE provides a legal basis for regulating digital information, its implementation remains constrained by unclear regulatory guidelines, uneven law enforcement, and the rapid development of digital technologies. The study finds that privacy protection requires not only legal provisions but also comprehensive digital governance, stronger data protection policies, and improved public digital literacy. Strengthening privacy rights under UU ITE is essential to ensure legal certainty, prevent misuse of personal data, and support digital trust among users in Indonesia’s evolving digital ecosystem.